Design and Evaluation of Visual Cues for Restoring and Guiding Visual Attention in Eye-Tracked VR - Woodworth, Jason W.; Yoshimura, Andrew; Lipari, Nicholas G.; Borst, Christoph W. (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Distraction can be a problem in VR training environments. We investigate 9 visual cues intended to guide or restore attention to objects of interest to mitigate distraction. A survey of related literature suggests a past focus on "search and selection" tasks to evaluate a cue's capability for guidance. We compare this to a new type of task that focuses on how to restore attention when a short distraction (e.g. a notification) shifts focus away from an object. Our study includes a guidance task in which subjects gaze at objects in a randomized order and a restoration task in which gaze sequences are interrupted by distraction events after which gaze must be returned to an object. Factors such as object spacing, gaze dwell time, and distraction distance and duration are varied. The results reveal different patterns of cue effectiveness for the restoration task than for conventional guidance. This may be attributed to knowledge that subjects have about the location of the object from which they were distracted. One implication for more complex distraction tasks considers that we expect them to be between the short distraction and regular guidance in terms of memory of object position. So, we speculate cue performance for other tasks would vary between the short distraction and guidance results. For restoration, some cues add complexity that reduces, rather than improves, performance. In addition to revealing the differences between guidance and restoration performance of cues, substantial depth is added beyond prior work by the broader range of conditions and cues included.